The Influence Of Aggressive Financial Reporting Of The Company Toward Aggressive Tax Reporting In Agricultural Companies - Wulan, Mulyaning; Ilhamdi, Ilhamdi; Qistiyah, Kunti Jeihan (Agregat: Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine the influence of aggressive financial reporting, ROA, DAR, and Size OF The Company toward Aggressive Tax Reporting (ATR) in agricultural companies listed in Daftar Efek Syariah (DES) during period 2013-2016. The sampling method is purposive sampling. The data analyzed using multiple regression for dated panel with significance level 5% (0,05). The choosing model test showed that model used in this study is the Fixed Effect Model (FEM). Simultaneously all independent variables from model had significant influence toward dependent variable (ATR). Partially aggressive financial reporting, ROA, and DAR that had significance influence toward ETR, while variable size had unsignificant influence. The research also showed that there is trade off between aggressive financial reporting and aggressive tax reporting.